ERAS in minimally invasive hepatectomy - Fung, Andrew K. Y. (Ann Hepatobiliary Pancreat Surg, 2020)
Open hepatectomy is associated with significant post-operative morbidity and mortality profile. The use of minimally invasive approach for hepatectomy can reduce the post-operative complication profile and total length of hospital stay. Enhanced recovery after surgery (ERAS) programs involve evidence-based multimodal care pathways designed to achieve early recovery for patients undergoing major surgery. This review will discuss the published evidence, challenges and future directions for ERAS in minimally invasive hepatectomy.